PENGARUH PROFITABILITAS, LIKUIDITAS, UKURAN PERUSAHAAN, TERHADAP NILAI PERUSAHAAN - Andrew Tandanu, Lukman Suryadi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study was to analyze the effect of profitability, liquidity and firm size on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period of 2016 - 2018. The method of sampling in this study was purposive sampling, in which 72 companies were selected as samples. Data processing techniques in this study use multiple regression analysis using the IBM SPSS Statistics 25 program. The results of this study indicate that profitability does not affect the firm value, liquidity does not have an influence to firm value, and firm size has a significant influence on firm value.